Importance of testing the internal consistency and construct validity of the Pittsburgh Sleep Quality Index (PSQI) in study groups of day and night shift workers: Example of a sample of long-haul truck drivers in South Africa. (January 2022) - Roche, Johanna; Vos, Alinda G.; Lalla-Edward, Samanta T.; Kamerman, Peter R.; Venter, WD. Francois; Scheuermaier, Karine
Abstract: Irregular work times promote inconsistent completion of the Pittsburgh Sleep Quality Index (PSQI) among shift workers. We aimed to demonstrate the importance of testing the internal consistency and construct validity of the PSQI and of the Epworth Sleepiness Scale (ESS) by presenting the methodology in a sample of long-haul truckers in South Africa. Internal consistency of the questionnaires was assessed by Cronbach's alpha (defined as raw alpha≥0.70), and construct validity by factor analysis. 302 participants (49.3%) reported at least one night shift/week. Overall, the PSQI and ESS's alpha were 0.42 and 0.85, respectively. The factors explained 19.6% of 57.0% of the variance. The PSQI's alpha was 0.46 in night shift workers and 0.38 in non-night shift workers. In this occupational group, the PSQI must be used with caution. Testing the internal consistency and construct validity among the assessed population seems necessary. Sleep questionnaires adapted to shift workers should be preferred. Highlights: The PSQI is not a reliable tool among long-haul truck drivers from Southern Africa. PSQI internal consistency and construct validity should be investigated among shift workers. Ergonomists should use sleep questionnaires adapted to shift workers.